2012
DOI: 10.1016/j.vaccine.2012.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in the CDC Anthrax Vaccine Adsorbed Human Clinical Trial

Abstract: These results do not favor an association between receipt of AVA and an altered health-related quality of life over a 42-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In studies from the Vaccine Analytic Unit and other groups published since 2010, no association was found between AVA receipt and the following chronic health conditions: reduction in health-related quality of life measures ( 46 ), multisystem illness ( 47 ), long-term disabilities ( 48 , 49 ), type 1 diabetes ( 50 ), atrial fibrillation ( 51 ), and diffuse connective tissue diseases ( 52 ). In one case-control study, an association was identified between AVA receipt and new-onset rheumatoid arthritis if a look-back period of 3 months was used (odds ratio [OR]: 3.93; 95% CI: 1.08–14.27).…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…In studies from the Vaccine Analytic Unit and other groups published since 2010, no association was found between AVA receipt and the following chronic health conditions: reduction in health-related quality of life measures ( 46 ), multisystem illness ( 47 ), long-term disabilities ( 48 , 49 ), type 1 diabetes ( 50 ), atrial fibrillation ( 51 ), and diffuse connective tissue diseases ( 52 ). In one case-control study, an association was identified between AVA receipt and new-onset rheumatoid arthritis if a look-back period of 3 months was used (odds ratio [OR]: 3.93; 95% CI: 1.08–14.27).…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Data from the UK and US suggest that anthrax vaccination prevents disease . Anthrax vaccination is considered safe . Injection site reactions occur in 47% of AVP recipients .…”
Section: Anthraxmentioning
confidence: 99%